2019
DOI: 10.1101/678797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Principles of self-organization and load adaptation by the actin cytoskeleton during clathrin-mediated endocytosis

Abstract: words)Force generation due to actin assembly is a fundamental aspect of membrane sculpting for many essential processes. In this work, we use a multiscale computational model constrained by experimental measurements to show that a minimal branched actin network is sufficient to internalize endocytic pits against physiological membrane tension. A parameter sweep identified the number of Arp2/3 complexes as particularly important for robust internalization, which prompted the development of a molecule-counting m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 135 publications
4
44
0
Order By: Relevance
“…In recent years, the Arp2/3 complex turned out to be of fundamental importance for numerous cellular processes, including actin-based cell edge protrusion during migration and various additional actin assembly processes at both plasma and intracellular membranes (Rotty et al, 2013;Molinie and Gautreau, 2018), as well as specific interactions of viral or bacterial pathogens with their host cells (Welch and Way, 2013). Interestingly, many of these processes, in particular those occurring at the plasma membrane, involve adaptive responses orchestrated by Arp2/3 complex to mechanical forces (Mueller et al, 2017;Akamatsu et al, 2020), as recently emphasized (Papalazarou and Machesky, 2020). Although the canonical complex is comprised of seven subunits throughout eukaryotic cell evolution, expression of functionally diverse or incomplete complexes - even within the same cell type – have also been described (Chorev et al, 2014;Abella et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…In recent years, the Arp2/3 complex turned out to be of fundamental importance for numerous cellular processes, including actin-based cell edge protrusion during migration and various additional actin assembly processes at both plasma and intracellular membranes (Rotty et al, 2013;Molinie and Gautreau, 2018), as well as specific interactions of viral or bacterial pathogens with their host cells (Welch and Way, 2013). Interestingly, many of these processes, in particular those occurring at the plasma membrane, involve adaptive responses orchestrated by Arp2/3 complex to mechanical forces (Mueller et al, 2017;Akamatsu et al, 2020), as recently emphasized (Papalazarou and Machesky, 2020). Although the canonical complex is comprised of seven subunits throughout eukaryotic cell evolution, expression of functionally diverse or incomplete complexes - even within the same cell type – have also been described (Chorev et al, 2014;Abella et al, 2016).…”
Section: Introductionmentioning
confidence: 93%
“…Akamatsu et al. [ 21 ] and Sun et al [ 22 ] recently modelled how Arp2/3-generated actin networks assist CME events, using agent-based modelling and quantitative experimental studies. They found that endocytic actin networks adapted to the changing landscape of membrane tension during the various stages of deformation and endocytic uptake of clathrin-coated endocytic vesicles ( Figure 1 ).…”
Section: Arp2/3 In Clathrin-mediated Endocytosismentioning
confidence: 99%
“…Many theoretical studies have attempted to estimate the forces required for endocytic membrane remodelling, proposing values over a range of two orders of magnitude (tens to thousands of pN; Akamatsu et al, 2020; reviewed in Carlsson, 2018; Lacy et al, 2018). Here, we have measured the force required for endocytic vesicle formation in yeast under normal and different genetically and environmentally perturbed conditions.…”
Section: Discussionmentioning
confidence: 99%